2018
DOI: 10.1111/his.13494
|View full text |Cite
|
Sign up to set email alerts
|

Podoplanin‐positive myofibroblasts: a pathological hallmark of pleuroparenchymal fibroelastosis

Abstract: Pathological differential diagnoses of pleuroparenchymal fibroelastosis (PPFE) include usual interstitial pneumonia (UIP) and pulmonary apical cap (PAC); however, there are no specific immunostaining makers to distinguish between these diseases. We performed immunohistochemistry using several pleural mesothelial cell-related markers, including cytokeratin-5/6, CAM5.2, WT-1, calretinin, desmin and podoplanin, for PPFE (n = 4), UIP (n = 10) and PAC (n = 3) lung sections. Among the examined markers, in PPFE and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Last, we found an accumulation of podoplanin-positive spindle cells in the fibrotic region of autopsied lungs. Enomoto et al reported that podoplanin-positive myofibroblasts might reflect mesothelial-to-mesenchymal transition, and this could be a pathological hallmark of iPPFE (38). Our findings suggest that a fibrotic process similar to iPPFE was also involved in the current case with post-HSCT PPFE.…”
Section: Discussionsupporting
confidence: 59%
“…Last, we found an accumulation of podoplanin-positive spindle cells in the fibrotic region of autopsied lungs. Enomoto et al reported that podoplanin-positive myofibroblasts might reflect mesothelial-to-mesenchymal transition, and this could be a pathological hallmark of iPPFE (38). Our findings suggest that a fibrotic process similar to iPPFE was also involved in the current case with post-HSCT PPFE.…”
Section: Discussionsupporting
confidence: 59%
“…One of the pathological characteristics of PPFE is lymphatic proliferation, which may be a compensatory event secondary to impaired lymphatic drainage (13). It is necessary to investigate whether or not subpleural consolidations on chest CT in the present case were associated with particular pathological findings, such as fibrosis and the confluence of granulomas; increases in elastic fibers, proliferation of podoplaninpositive myofibroblasts (14), and lymphatic proliferation (13) as seen in PPFE cases; and increases in smooth muscle and collagenous fibers as seen in idiopathic pulmonary fibrosis/usual interstitial pneumonia cases.…”
Section: Discussionmentioning
confidence: 84%
“…Here we have shown co-localization of α-SMA and smoothelin in SUI myofibroblast. Myofibroblasts that co-express α-SMA and smoothelin ( Lepreux et al, 2013 ), podoplanin ( Braun et al, 2011 ; Nazari et al, 2016 ; Enomoto et al, 2018 ; Hirayama et al, 2018 ), cadherin ( Hinz et al, 2004 ; Bowler et al, 2018 ), tenascin ( Katoh et al, 2020 ) or collagen I ( Zhang et al, 1994 ) have been found during the fibroblast-to-myofibroblast transition and are associated with advanced stages of fibrosis in several diseases. All these myofibroblast markers have also been found in the control group of women, as described by others for women operated on for other gynecological indications ( Ruiz-Zapata et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%